The school climate at the Talent Schools from the point of view of the Teachers and Management Staff - A Field Study in all Homs, Tartous, and Lattakia (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This research aimed at recognize the school climate at the Talent Schools in Syria Arab Republic from the point of view of the Teachers and Management Staff, it also tries to identify the differences in their opinions based on the following variables: (job title, educational and scientific qualifications and years of experience). To achieve this research, questionnaire was designed including (56) items included school climate at the Talent Schools; distributed to the five areas (Management, Teachers, Curricula and Methods of Instruction, examination, teaching Environment), then applied to a sample of (222) Teachers and Management Staff for the academic year 2016/2017. The present research used the descriptive analytical approach. Validity of the questionnaire was established though a jury of (7) of the teaching staff of educational at Damascus and Tishreen universities. Pilot sample consisted of (22) Teachers and Management Staff, Reliability was established by Cronbach – Alpha Reliability at lest (0.775). The final results showed that the school climate at the Talent Schools in Syria was middle degree. In fact there are no found differences about the school climate at the Talent Schools according to variables (job title, and years of experience), but there are found differences according to variable educational and scientific qualifications. The Research suggestions to developed the school climate at the Talent Schools, as well as carrying further researches about the problems of the Gifted Students.